Students' Perceptions of The Four Indicators of Religious Moderation in Arabic Textbooks: Corpus-based Critical Discourse Analysis - Jamalin, Fakron (Universitas Islam Indonesia, 2024)
A contextual Arabic textbook was compiled as a religious moderation program in UIN Maulana Malik Ibrahim, Indonesia. The moderation program was initiated by the Ministry of Religious Affairs. A textbook showing Indonesian culture was developed to differentiate Arabic textbooks from other countries, such as Germany and Saudi Arabia. The textbook contains four distinct indicators. This study explores the concordance and collocation of four indicators of religious moderation in Arabiyah Lil Hayah (ALH). It also investigated students’ perceptions of the four indicators. Employing corpus-based critical discourse analysis, this study collected a corpus from the ALH book on student perceptions in txt form. This study identified that the indicator of National Commitment is present in several contexts, such as August 17, Islamic organizations, and elections. The Tolerance indicator is represented by the different opinions of the four madzhabs and the motto of Bhinneka Tunggal Ika. The teaching of non-violence was described in the Hajar Aswad incident in Makkah. Local culture was introduced in the context of culture, ethnicity, and traditional food. Students use a variety of sentences to express their perceptions, including cause-and-effect, supposition, and rhetorical forms. When the discourse is personally relevant, pronouns are used to reflect this connection, with their expression of identity often aligned with their social community or gender, such as affiliations with NU (Nahdlatul Ulama) or their identity as women.